Effects of residence time and mixing regimes on the precipitation characteristics of CaF2 and MgF2 from high ionic strength sulphate solutions - Eksteen, Jacques; Pelser, M.; Onyango, M.; Lorenzen, L.; Aldrich, Chris; Geogalli, G. (Elsevier Science BV, 2008)
The presence of calcium (Ca) and magnesium (Mg) in the hydrometallurgical processing of base metals is responsible for the contamination of the final product, high energy consumption and large bleed streams during electrowinning. This paper elaborates on the use of ammonium fluoride to precipitate Ca and Mg as their respective fluoride minerals, namely, fluorite and sellaite. The effects of residence time and mixing regimes on crystal growth characteristics and the derived particle size distributions were investigated. The mixing levels in a typical mixed-suspension–mixed-product-removal (MSMPR) were represented by 3 possible mixing regimes; micro-, meso- and macromixing. A three-zone experimentalsetup was used to study the effects of the micro-, meso-, and macromixing on the crystal size distribution and filterability of fluorite and sellaite. The ionic strength of the sulphate solutions used was similar to those found in base metal leach circuits. As a result, SEM-images of the formed crystals depicted stable agglomerates of around 20 µm consisting of smaller particles in the range of 1–3 µm. The filter cake resistance was found to be around 4.0×109 m3/kg m2, and did not vary significantly for the experimental conditions chosen for the 3-zone experiment. The residence time did have a small but significant effect on increasing the mean and median of the particles size distributions. Increase in both macromixing and micromixing resulted in a decrease of the mean particle size, while no significant difference was noticed for mesomixing of the reactant streams. © 2008 Published by Elsevier B.V.